Stability Analysis and Numerical Simulation of a Diffusive Prey-Predator Holling Type II Model. Issue 1 (June 2021) - Satria, A; Putri, A R; Syafwan, M
Abstract: The prey predator interaction is fundamental and important process in a population dynamic. In this paper, a diffusive prey predator holling type II model considering limitation of the prey growth is presented. The model consists two distinct populations. Model is a nonlinear system of partial differential equations which is a initial boundary value problem. The behaviour solution of the model was analyzed by analyzing stability of the critical point. In solving this system, we use Homogeneous Neumann boundary conditions. Numerical solution was determined by using finite difference method. The results show that the diffusive model illustrates a spreading population over a limited area.